The Metabolic Basis of Fat Tail Distributions in Populations and Community Fluctuations - Segura, Angel M.; Perera, Gonzalo (Frontiers in Ecology and Evolution, 2019)
Unveiling the mechanisms that molds populations fluctuations is central for understanding the dynamic of pest outbreaks, harmful algal blooms or extinction risk. We hypothesize that metabolic restriction to maximum population abundance shapes single population and community fluctuations. Here, we derive a formal theoretical model linking metabolic limits to maximum population abundance with the distribution of fluctuations of single populations and communities. First, we show that the emergence of fat tails in the distribution of single population fluctuations is caused by the metabolic effect on maximum population abundance of periodic changes in resource supply or temperature. Second, we show an explicit link between single population fluctuations and the Laplace distribution of aggregated community fluctuations. Third, we derive a general relationship between population variance and body mass (called variance-mass allometry; VMA). This framework provides a theoretical mechanism to explain fat-tailed distributions of population fluctuations. It also predicts a double exponential or Laplace distribution of community fluctuations when the range of body size in the community is large. Finally, it provides a generalization of the VMA model which is able to generate theoretical predictions about patterns of variability among species lifestyles. This framework provides specific theoretical predictions that can be benchmarked against alternative competing models and empirical data, hence furthering our understanding about how metabolism determines abundance fluctuations.